TAMAN LALU LINTAS DI TABALONG - Ghyfari, Khairunnisa; Anhar, Pakhri (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Based on population projections, it is estimated that Indonesia will get additional demographics which would increase the transportation density, possibly increasing number of traffic accidents. Response to this condition is to design a traffic park. Traffic Park in Tabalong is a recreational and educational area designed to develop traffic awareness from an early age by providing real traffic simulation experience. This design uses the simulation method in architecture. As the solution, the concept of Education-Recreation is applied so the design can be used as fun learning tool for children and recreation for the whole family.